PENGARUH KEMUDAHAN TRANSAKSI NON-TUNAI TERHADAP SIKAP KONSUMTIF MASYARAKAT KOTA MAKASSAR - Mariesa Giswandhani; Amalia Zul Hilmi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Hasanuddin, 2020)
Communication technology is increasingly developing and providing convenience to every user. Modern society is also required to be fast and easy, by it the transformation of payments in the form of cash has turned into noncash due to technological advances. The ease of this service is realized to be able to change the lifestyle or behavior of the community, especially in Makassar City. This study aims to determine the effect of the convenience of si technology, especially non-cash transactions, on consumptive behavior. This study uses aquantitative-exploratory method with a sample of 100 respondents who are the people of Makassar city. Based on the test results both simultaneously and partially, the research results show that there is a significant direct influence between the ease of non-cash transactions referring to its dimensions, namely clear and easy to understand, does not require long thinking, is easy to use, can be controlled, is easy to be skilled and flexible towards consumptive attitudes Makassar city people.